A novel method for the development of a carbon quantum dot/carbon nitride hybrid photocatalyst that responds to infrared light irradiation1. Issue 25 (7th July 2015) - Guo, Yong; Yao, Pinjiang; Zhu, Dongqiang; Gu, Cheng
<x xml:space="preserve">Abstract</x> A facile strategy has been developed to combine carbon quantum dots and a hydrophobic carbon nitride photocatalyst together to form an infrared-responsive photocatalyst. The photodegradation experiment has confirmed that the obtained material can effectively degrade methyl orange under infrared light irradiation.